Cacar di Jawa: dua orde dalam penaklukan pagebluk - Zanuar Rivaldi; Shelin Puspa Arum; Royya Zahrotul Mala (Universitas Negeri Malang, 2021)
Smallpox was one of the epidemics that hit Java since the beginning of the Dutch colonial rule and infected almost all of Java in the early 19th century. Smallpox vaccination is the oldest preventive effort to tackle this disease. During the Dutch and British rule, the smallpox epidemic was resolved by the spread of smallpox vaccination efforts in Java. The Organization for implementing vaccination continued to be developed and refined until the beginning of the 20th century. Thanks to this, the Java region was almost free from the smallpox epidemic. Before the Dutch colonial period ended and smallpox only appeared in a few places as a sporadic case. During the independence period, smallpox disease was invaded in the Old Order and New Orders due to irregular vaccination during the Japanese occupation and the war for independence. The adoption of the mass-enacting policy in 1951 succeeded in inhibiting the spread of smallpox outbreaks but left behind pockets of infection in several areas. Efforts to eradicate smallpox in the form of mass vaccination continue to be conducted despite obstacles until finally, the WHO (World Health Organization) declared that Indonesia was free of smallpox on April 25, 1974. The main focus of this study was to explain how the Indonesian government’s policies and economic constraints and impacts especially on the Old Order and New Order in overcoming the smallpox epidemic in Java.Cacar merupakan salah satu epidemi yang melanda Jawa semenjak awal masa pemerintahan kolonial Belanda dan menjangkiti hampir seluruh wilayah Jawa pada awal abad ke-19. Vaksinasi cacar atau pencacaran merupakan upaya preventif tertua untuk menanggulangi penyakit ini. Pada masa pemerintahan Belanda dan Inggris, epidemi cacar dapat terselesaikan dengan adanya upaya pencacaran yang mulai diperluas di Jawa. Organisasi pelaksanaan pencacaran terus dikembangkan dan disempurnakan hingga awal abad ke-20. Berkat hal tersebut wilayah Jawa hampir terbebas dari wabah cacar. Sebelum masa penjajahan Belanda berakhir penyakit cacar hanya timbul di beberapa tempat sebagai kasus sporadik. Pada masa kemerdekaan, penyakit cacar kembali merebak di masa Orde Lama dan Orde Baru akibat vaksinasi yang tidak teratur selama pendudukan Jepang dan perang kemerdekaan. Penerapan kebijakan pencacaran masal di tahun 1951 berhasil menghambat penyebaran wabah cacar namun meninggalkan kantong-kantong infeksi di beberapa daerah. Upaya pemberantasan penyakit cacar berupa vaksinasi masal terus dilakukan meskipun mengalami berbagai kendala hingga akhirnya WHO (World Health Organization) menyatakan bahwa Indonesia bebas cacar pada 25 April 1974. Fokus utama kajian ini berupaya menjelaskan bagaimana kebijakan pemerintah Indonesia berikut juga kendala dan dampak secara ekonomi khususnya pada masa Orde Lama dan Orde Baru dalam mengatasi epidemi penyakit cacar di Jawa.